Disparate Dynamics of Gene Body and cis-Regulatory Element Evolution Illustrated for the Senescence-Associated Cysteine Protease Gene SAG12 of Plants - Vatov, Emil (Plants (Basel), 2021)
Gene regulation networks precisely orchestrate the expression of genes that are closely associated with defined physiological and developmental processes such as leaf senescence in plants. The Arabidopsis thaliana senescence-associated gene 12 (AtSAG12) encodes a cysteine protease that is (i) involved in the degradation of chloroplast proteins and (ii) almost exclusively expressed during senescence. Transcription factors, such as WRKY53 and WRKY45, bind to W-boxes in the promoter region of AtSAG12 and play key roles in its activation. Other transcription factors, such as bZIPs, might have accessory functions in their gene regulation, as several A-boxes have been identified and appear to be highly overrepresented in the promoter region compared to the whole genome distribution but are not localized within the regulatory regions driving senescence-associated expression. To address whether these two regulatory elements exhibiting these different properties are conserved in other closely related species, we constructed phylogenetic trees of the coding sequences of orthologs of AtSAG12 and screened their respective 2000 bp promoter regions for the presence of conserved cis-regulatory elements, such as bZIP and WRKY binding sites. Interestingly, the functional relevant upstream located W-boxes were absent in plant species as closely related as Arabidopsis lyrata, whereas an A-box cluster appeared to be conserved in the Arabidopsis species but disappeared in Brassica napus. Several orthologs were present in other species, possibly because of local or whole genome duplication events, but with distinct cis-regulatory sites in different locations. However, at least one gene copy in each family analyzed carried one W-box and one A-box in its promoter. These gene differences in SAG12 orthologs are discussed in the framework of cis- and trans-regulatory factors, of promoter and gene evolution, of genetic variation, and of the enhancement of the adaptability of plants to changing environmental conditions.